A De Novo Missense Variant in POU3F2 Identified in a Child with Global Developmental Delay - Westphal, Dominik Sebastian; Riedhammer, Korbinian Maria; Kovacs-Nagy, Reka; Meitinger, Thomas; Hoefele, Julia; Wagner, Matias (Neuropediatrics, 2018)
Many genetic and nongenetic causes for developmental delay in childhood could be identified. Often, however, the molecular basis cannot be elucidated. As next-generation sequencing is becoming more frequently available in a diagnostic context, an increasing number of genetic variations are found as causative in children with developmental delay.We performed trio exome sequencing in a girl with developmental delay and minor dysmorphological features. Using a filter for de novo variants, the heterozygous missense variant c.812A>T, p.(Glu217Val) was found in the candidate gene POU3F2 in our patient.POU3F2 plays an important role in neuronal differentiation and hormonal regulation. To date, it has not been associated with monogenic disorders. Studies on Pou3f2 knockout mice highlighted the importance of this protein in the development of the brain. Furthermore, microdeletions with an overlapping region including only POU3F2 and FBXL4 were linked to developmental delay in six unrelated families. Therefore, POU3F2 is a strong candidate gene for developmental delay, although functional assays proving this assumption still have to be done.
Keywords: de novo; missense; POU3F2; developmental delay; dysmorphological; exome sequencing